In the zone : helping children rise to the challenge of learning - Lansdown, Mike (Critical Publishing, 2020)
In the Zone argues that challenge is an essential element of true learning, without which there can be no progress. It brings together supportive materials to encourage teachers to reflect on their present practice, take sensible risks with their teaching, and understand the importance of enjoyment and engagement for both teachers and pupils.